Out of sight, out of mind? Income inequality proximity and happiness in urban Mexico - Cobos Cabral,Francisco (2025)
Income inequality is typically assumed to be a societal problem. Yet, empirical evidence remains inconclusive on whether inequality reduces individuals’ well-being or not. This study uses data on national-, state-, and city-level inequality measures in Mexico to observe how these relate to changes in self-reported well-being across 12 years. The analysis reveals that the relationship between happiness and inequality depends on the geographical level at which inequality is measured and can be mediated by individuals’ income. National income inequality is negatively associated with life satisfaction in Mexico, although the rich are considerably less affected by it. On the other hand, state-level and city-level inequality are not significantly related to life satisfaction for either income group. These relationships are maintained after being tested simultaneously, implying that each proximity level of inequality captures an independent effect on life satisfaction. This may indicate that the mechanisms driving the inequality-happiness relationship are different depending on the geographical level at which inequality is observed. Concretely, the findings suggest that the positive effects of inequality are more likely to be experienced for inequalities at closer proximity levels. This calls for increased nuance and theoretical consideration when measuring the effects of inequality on individuals’ well-being.
Keywords: income inequality; happiness; wellbeing; Mexico; life satisfaction; geographical proximity; multilevel